Peptidoglycan endopeptidase MepM of uropathogenic Escherichia coli contributes to competitive fitness during urinary tract infections - Huang, Wen-Chun; Dwija, Ida Bagus Nyoman Putra; Hashimoto, Masayuki; Wu, Jiunn-Jong; Wang, Ming-Cheng; Kao, Cheng-Yen; Lin, Wei-Hung; Wang, Shuying; Teng, Ching-Hao (BMC microbiology, 2024)
Urinary tract infections (UTIs) are common bacterial infections, primarily caused by uropathogenic Escherichia coli (UPEC), leading to significant health issues and economic burden. Although antibiotics have been effective in treating UPEC infections, the rise of antibiotic-resistant strains hinders their efficacy. Hence, identifying novel bacterial targets for new antimicrobial approaches is crucial. Bacterial factors required for maintaining the full virulence of UPEC are the potential target. MepM, an endopeptidase in E. coli, is involved in the biogenesis of peptidoglycan, a major structure of bacterial envelope. Given that the bacterial envelope confronts the hostile host environment during infections, MepM's function could be crucial for UPEC's virulence. This study aims to explore the role of MepM in UPEC pathogenesis. MepM deficiency significantly impacted UPEC's survival in urine and within macrophages. Moreover, the deficiency hindered the bacillary-to-filamentous shape switch which is known for aiding UPEC in evading phagocytosis during infections. Additionally, UPEC motility was downregulated due to MepM deficiency. As a result, the mepM mutant displayed notably reduced fitness in causing UTIs in the mouse model compared to wild-type UPEC. This study provides the first evidence of the vital role of peptidoglycan endopeptidase MepM in UPEC's full virulence for causing UTIs. MepM's contribution to UPEC pathogenesis may stem from its critical role in maintaining the ability to resist urine- and immune cell-mediated killing, facilitating the morphological switch, and sustaining motility. Thus, MepM is a promising candidate target for novel antimicrobial strategies.